Import penetration and manufacturing employment: Evidence from Africa - Solomon Owusu; Gideon Ndubuisi; Emmanuel. B. Mensah (United Nations University (UNU), Maastricht Economic and Social Research Institute on Innovation and Technology (UNU-MERIT), 2022)
Exposure to import competition can either help or hurt domestic employment creation. There is, however, a dearth of cross-country empirical evidence assessing labor market effects of import penetration in Africa. This paper fills this gap. Using manufacturing industry and establishment-level data across 20 African countries and estimating a conditional and unconditional labor demand model, we find an unambiguous employment creation effect of intermediate good import penetration, whilst final good import penetration has a negative, or at best, an insignificant effect on employment. Splitting intermediate good import penetration into their origins, we find that intermediate good import penetration from developed (developing) countries is employment increasing (reducing). Further analyses reveal that the positive employment effects of intermediate import penetration from developed countries disproportionately benefit the skilled workforce. We also find that industries with higher absorptive capacity stand to gain more from intermediate good import penetration from developed countries, with the negative effects of intermediate good import penetration from developing countries also diminished for these industries. We discuss the implications of our findings.
Keywords: F11; F14; L25; L60; O14; O15; 330; Import Penetration; Employment; Absorptive Capacity; Manufacturing; Africa